Digital Marketing: A critical review on its Advancement and Evolution - Das, Jyotiranjan (International Journal of Psychosocial Rehabilitation, 2019)
This paper offers insights into some current and future advertising patterns. The material is based on recent research and what’s going on in the business world. The paper is focused on secondary data. The paper is based on existing sources of literature and the internet. The numerous documents, studies, reports, newspapers, magazines, websites and internet data were examined. In India, witnessing a radical change in digitalization. Consumers are searching for more online to find the best deal for sellers in India compared to traditional or modern methods. In this report, recognizing that businesses could benefit from digital marketing such as influencer marketing, search engine optimization (SEO), search engine marketing (SEM), product management, e-commerce marketing, content marketing, campaign marketing, and social media marketing, social media optimization, direct e-mail marketing, display advertising, e-books, optical disks. It demonstrates that all linked through WhatsApp and twitter, and the increasing use of social media creates new opportunities for digital marketers to attract customers through digital technology. Consumer awareness is critical because it offers a deeper understanding of what drives users to create a product or store content. Digital marketing is cost-effective and has a significant business impact. On the basis of this report, it can also be argued that understanding that social media sites use the target market of a business is another key factor in ensuring successful online marketing. It is important to evaluate the efficacy of Internet marketing in relation to different businesses. The research can be applied further to equate the methods of internet marketing with those common to different businesses.